China's debt problem and rising systemic risks: Impact of the global financial crisis and structural problems - Yuefen Li (South Centre, 2017)
The fast expansion of China's debt, in particular corporate and local government debt, has attracted international attention and has also become a major concern of China's policy makers. Even though China can tolerate a higher debt level than many other emerging and developing economies owing to the sheer size and other special features of the Chinese economy, systemic risks for financial stability have been rising since the global financial crisis and the cushions built in the past decades to withstand a higher debt level have also been weakened. This paper reviews the evolution of China's debt built-up, examines reasons behind this trend and factors leading to the rising systemic risks including the expansion of shadow credits, increasing interlinkages between the stock and bond markets as well as the banking sector, and declining returns of investment from the corporate sector. The paper also makes recommendations for addressing the challenges to maintain financial stability and economic growth.
Keywords: 300; Haushaltsdefizit; Öffentliche Schulden; Systemrisiko; Finanzkrise; Wirtschaftswachstum; China